METRIC-GIS: An advanced energy balance model for computing crop evapotranspiration in a GIS environment. (September 2020) - Ramírez-Cuesta, J.M.; Allen, R.G.; Intrigliolo, D.S.; Kilic, A.; Robison, C.W.; Trezza, R.; Santos, C.; Lorite, I.J.
Abstract: A novel ArcGIS toolbox that applies the Mapping Evapotranspiration with Internalized Calibration model was developed and tested in a semi-arid environment. The tool, named METRIC-GIS, facilitates the pre-processing operations and the automatic identification of potential calibration and pixels review. The energy balance components obtained from METRIC-GIS were contrasted with those from the original METRIC version (R 2  = 1; RMSE = 0 W m −2 or mm day −1 for ETc ) Additionally, an irrigated scheme located at southern Spain was considered for assessing Kc variability in the maize fields with METRIC-GIS. The identified spatial variability was mainly due to differences in irrigation regimes, crop management practices, and planting and harvesting dates. This information is critical for developing irrigation advisory strategies that contribute to the area sustainability. The developed tool facilitates data input introduction and reduces computational time by up to 50%, providing a more user-friendly alternative to other existing platforms that use METRIC. Highlights: Development of an ArcGIS toolbox for ETc estimation from remote sensing, METRIC-GIS. METRIC-GIS has been successfully tested in a semi-arid environment. The tool has a user-friendly interface for assessing spatially distributed ETc maps. METRIC-GIS eases input introduction and reduces computational time and user errors.